Towards a New Euro Crisis? - Paul De Grauwe (Intereconomics)
Abstract There is thus a fundamental credibility issue about the willingness of the ECB to be a lender of last resort in the government bond markets. This will continue to make the eurozone a fragile construction. As a result, the possibility of a future euro crisis cannot be excluded.